Critical factors influencing construction technology adoption: A multivariate analysis - Fakhira, Khudzari; Rahimi, A. Rahman; Ayer, Steven K; Ahmad Tarmizi, Haron (AIP Publishing, 2023)
The construction sector is one of the long-established sectors in the world. However, the sector has struggled to acquire effective and basic technology on job sites. This is where the value of new construction technology is critical in driving industry quality and productivity. However, its implementation is at a low level in numerous countries and despite a well-understood lack of technological adoption, the factors influencing this trend are not yet understood. Hence, it is vital to have a thorough understanding of what influences its adoption. This study aims to identify the critical factors influencing technology adoption in the Architecture, Engineering, and Construction (AEC) industry. First, semi-structured interviews with industry practitioners and a systematic literature review of 211 articles yielded 35 factors influencing construction technology adoption. Then, data on the 35 factors were collected through a survey among AEC industry practitioners. In total, 147 valid responses were received and analyzed using mean ranking analysis and exploratory factor analysis. The ranking analysis results indicated that 14 critical factors had been identified. In contrast, through factor analysis, 10 out of 14 critical factors have been grouped into three underlying components: organizational resources, goals, and strategy. The findings could provide construction industry professionals with a useful reference to promote technological adoption in the construction industry.